CONSIDERING THE ELDERLY’S NEEDS IN DEVELOPING NURSING HOME DESIGN - MANURUNG Parmonangan (Dimensi: Journal of Architecture and Built Environment, 2016)
Statistics show that the elderly people population has increased every year, which makes the role of the nursing home, becomes very important. However, most nursing home has not been able to meet the needs of the elderly who have different needs due to changes in their physical and psychological abilities. This research was conducted at two nursing homes and aims to find the design changes and design development that occur to accommodate the needs of the elderly. A descriptive qualitative was employed, and in-depth interviews, field observation, literature reviews, and field measurements were conducted for collecting data. The data was coded and analysed using descriptive qualitative content approach. The results showed some changes were developed to meet the needs of the elderly as they experience changes in physical and psychological condition. The original design did not meet the need of elderly residents, therefore some development had been made. Design developments have already met and supported the activities of the elderly residents